Sistem Pakar Berbasis Web Menggunakan Metode Forward Chaining Untuk Mendiagnosa Penyakit Pulpa Dan Periapikal - Irfan Mahendra; Fadhilah Fadhilah; Ilfa Khairina (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2019)
Pulp and periacal disease is happening in Indonesia. This is because knowledge and people awarness to take care their dental health is in low level, so that a few of people in Indonesia do not know types, symptoms, and the solution, how to resolve the problem. Altough pulp and periacal disease have a bad impact like the patient's quality of life. Besides the cost of expensive dental care and have an impact on a person's overall health, such as can cause catastrophic diseases such as stroke, heart desease, and kidney. Based on these conditions, very important to make a web-based expert system to diagnose this problem with forward chaining methode. The expert system is created using Dreamweaver C56, PHP, CSS, and MySQL. Through this system application, people will find out the information and get consultations about pulp and periapical disease easily and quickly, so that it can be dealt with quickly and correctly.